Assessing the Influence of Financial Literacy and Economic Independence on Investment Decisions - Khadka, Ajaya Kumar (Nepal Journal of Multidisciplinary Research, 2023)
This study examines the variables influencing individual investors' decisions to make investments in the fast-paced financial landscape of Nepal. Two main goals were investigated: first, the relationship between financial literacy, investment decisions, and economic independence was explored; second, the effects of these aspects were examined in detail. The results show a robust positive association between financial literacy and wise decision-making, as well as between investment decisions and economic independence. Its importance was highlighted when it was found that economic independence strongly predicted investment decisions. Furthermore, financial literacy was shown to be an essential aspect impacting investing preferences. These findings underscore the significance of financial education and empowerment for individual investors in Nepal. Prospective avenues for investigation comprise delving into cultural impacts, evaluating the effectiveness of financial literacy initiatives, and examining the effects of nascent FinTech platforms on investing choices. This research adds to our understanding of the dynamics of investments in Nepal's changing financial system and provides valuable information for policymakers and investors.